Al-Kalimât Al-Bûgîsiyyah Dzât Asl ‘Arabiy Fî Mu’jam Al-Lughah Al-Bûgîsisiyyah Wa Al-Istifâdatu Minhâ Fî Ta’lîm Al-Lughah Al-‘Arabiyyah Lî Al-Bigîsiyyîn Al-Mubtadiin Harf “N” Ilâ “Y” Namûdzajan - Mulkiah; Fahmi Ridha (Mauriduna: Journal of Islamic Studies, 2021)
تهدف هذه الدراسة إلى التعرف على كشف الكلمات البوغيسية ذات أصل عربي في معجم للغة البوغيسية من حرف N إلى Y ، ومعرفة تغيرات التي تحصل على اللغة العربية بعد دخولها إلى اللغة البوغيسية، وكيفية الاستفادة منها في تعليم اللغة العربية.والمنهج الذي سلكتهه الباحثة هو منهج الوصفي التحليلي. والنتائج التي وصلت إليها الباحثة من خلال هذه الدراسة هي وجود الكلمات البوغيسية ذات أصل عربي في معجم اللغة البوغيسية من حرف N إلى Y وبلغ عدد الكلمات 65 كلمة. واكتشفت الباحثة أن الكلمات التي تدخل إلى اللغة البوغيسية لم تبقى حالتها من الناحية النطقية والدلالية وإنما يكون فيها تغيرات من حيث الصيغة والمعنى. وهذا يكون على حسب زيادته ونقصانه، ولقد قسمت الباحثة إلى أربعة أقسام وهي :الأول:كلمات العربية بقيت معانيه في اللغة البوغيسية، الثاني:كلمات العربية اتسعت معانيها في اللغة البوغيسية،الثالث:كلمات العربية ضاقت معانيها في اللغة البوغيسية، الرابع:كلمات العربية انتقلت معانيها في اللغة البوغيسية. ثم استفادة هذه الكلمات بوضعها في الحوار والنص والتدريبات لتكون نموذجا مقترحا في تعليم اللغة العربية للبوغيسيين المبتدئين. This study aims to determine the vocabulary of the Bugis language originating from Arabic in the Bugis language dictionary from the lettersN to Y, and to determine the changes that occur in Arabic after entering the Bugis language, and how to implicate them in teaching Arabic for beginners. The study uses descriptive analysis method,This study proves the exsistence of Bugis sentence originating from Arabic in the Bugis language dictionary, while the number of words reaches 65 words.The researcher found that the vocabulary entered into Bugis langiage was not fixed in logical and semantik terms, but there were changes in terms of form and meaning. This vocabulary can be grouped into fourt part, the first is the vocabulary of the Bugis language that does not change its meaning from the meaning of Arabic, the second vocabulary extend its meaning, the third vocabulary narrow its meaning, the fourth vocabulary changes its meaning. Which then makes use of this vocabulary by presenting examples of the use of the vocabulary into conversations, readings, and evaluation questions wich serve as sugested examples for learning Arabic for beginners from Bugis students.